Cytogenetic and molecular characterization of Speothos venaticus specimens - doi: 10.4025/actascibiolsci.v32i4.6775 - Carvalho, Thaís Lima; Curi, Rogério Abdallah; Santiloni, Valquíria; Chieregatto, Cleyde Angélica Ferreira da Silva; Rocha, Guaracy Tadeu; Mota, Lígia Souza Lima Silveira da (Acta Scientiarum. Biological Sciences, 2010)
The bush dog (Speothos venaticus) is a South American canid, included in the IBAMA (Brazilian Institute of Environment and Renewable Natural Resources) official list of animals threatened with extinction, in the vulnerable category. As a preservation and conservation strategy, specimens kept in captivity by Brazilian Institutions are monitored by a management plan. In order to characterize and analyze the genetic variability of bush dog specimens, a cytogenetic analysis was carried out, and microsatellite data were also obtained through the use of 15 primers, originally developed for the domestic dog (Canis familiaris). All tested primers showed transferability and amplified fragment sizes similar to those described for the canine genome. From the total number of primers, eight were tested, and presented two polymorphic regions. Regarding cytogenetic analysis, one of the animals had chromosomal mosaicism, disqualifying it as a reproducer to form stocks. Thus, we concluded that the genetic evaluation of wild animals kept in captivity provides data that can help with the practice of exchange between different institutions, avoiding problems in the reproductive capacity of the breeding stock.